2007
DOI: 10.4028/www.scientific.net/amr.18-19.303
|View full text |Cite
|
Sign up to set email alerts
|

I-V Characteristics for Bifacial Silicon Solar Cell under a Magnetic Field

Abstract: In this work, the influence of magnetic field on I-V characteristics of bifacial silicon solar cell n+-p-p+ structure is studied under constant multispectral illumination. After resolution of continuity equation related to photogenerated minority carriers’ density in the base region of this cell, MATLAB numerical simulations of excess minority carriers’, photocurrent densities and junction photovoltage profiles, have been developed with magnetic field in the bulk of the base region. In the same way, the IV cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 2 publications
1
17
0
Order By: Relevance
“…These two models permit also to calculate the excess minority carriers density, the photocurrent I [5], the phototension V [5], the solar V and P-V characteristics [5], the intrinsic junction recombination velocity (Sf0) [1,2], the real [1,2], the series and shunt resistances [5] and the diffusion capacitance solar cell's efficiency. Considering these two dimensions, effects of magnetic and electric fields and the irradiation on the electrical solar cell parameters are also studied [7,8]. In [3], authors used the columnar grains model and concluded that the solar cell's junction could be considered as a plane capacitor with two identical plane electrodes separated by an extension region width which de the dynamic junction velocity (SF), the grain size, the grain boundary recombination velocity and the wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…These two models permit also to calculate the excess minority carriers density, the photocurrent I [5], the phototension V [5], the solar V and P-V characteristics [5], the intrinsic junction recombination velocity (Sf0) [1,2], the real [1,2], the series and shunt resistances [5] and the diffusion capacitance solar cell's efficiency. Considering these two dimensions, effects of magnetic and electric fields and the irradiation on the electrical solar cell parameters are also studied [7,8]. In [3], authors used the columnar grains model and concluded that the solar cell's junction could be considered as a plane capacitor with two identical plane electrodes separated by an extension region width which de the dynamic junction velocity (SF), the grain size, the grain boundary recombination velocity and the wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 1, we present, a 3D model of an n + -p-p + type of a bifacial silicon solar cell [19,20] under magnetic field [21][22][23].…”
Section: Theorymentioning
confidence: 99%
“…SZE 1981) in one side and N + -N-P + structure (or vice versa) for double sides named bifacial silicon solar cell (S. Madougou et al 2004Madougou et al , 2005aMadougou et al , 2005bMadougou et al , 2007aMadougou et al et 2007b. Silicon solar cells have all contacts on the back of the cell.…”
Section: Silicon Solar Cellsmentioning
confidence: 99%
“…The photocurrent density I at the junction of solar cell is obtained from the excess minority carriers density of each illumination mode as follows (S. Madougou et al 2004Madougou et al et 2007a:…”
Section: Electrical Parameters 411 Photocurrentmentioning
confidence: 99%